Studi Komparatif Kebijakan dan Praktik Pemerintahan dalam Implementasi Program Desa Antikorupsi - Rifa Fazal Muttaqun; Nugraheni Arumsari (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The implementation of the Anti-Corruption Village Program initiated by the Corruption Eradication Commission (KPK) is analyzed through a comparative study of four villages: Logede Village (Kebumen), Kedungsumber Village (Bojonegoro), Kamang Hilia Nagari (Agam), and Karangsewu Kalurahan (Kulon Progo). This research employs a descriptive qualitative approach based on literature study to illustrate the differences in policies, practices, as well as supporting and inhibiting factors in applying the program’s five key indicators: governance, public services, supervision, community participation, and local wisdom. The analysis shows that the success of the program is strongly influenced by integrity-based leadership, active community involvement, supportive local regulations, and the strengthening of cultural values. Although each village has shown positive achievements, several challenges remain, such as limited technological infrastructure, the absence of specific anti-corruption regulations, and low participation from vulnerable groups. This program proves that eradicating corruption at the village level requires synergy between village governments, the community, and the KPK to foster clean and transparent governance.